Liver synthesis function in chronic asymptomatic or oligosymptomatic alcoholics: correlation with other liver tests - Borini, Paulo; Guimarães, Romeu Cardoso (Revista do Hospital das Clínicas, 1999)
Liver function and its correlation with bilirubin and hepatic enzymes were evaluated in 30 male chronic asymptomatic or oligosymptomatic alcoholics admitted into the psychiatric hospital for detoxification and treatment of alcoholism. Hypoalbuminemia, lowered prothrombin activity, hypotransferrinemia and hypofibrinogenemia were detected in 32 %, 32 %, 28 %, and 24 % of patients, respectively. Transferrin was elevated in 8 %. Greater prevalence of hyperbilirubinemia was found in patients with lowered prothrombin activity, hypofibrinogenemia, or hypotransferrinemia. No correlation was found between serum bilirubin or aminotransferase levels and normal or elevated albumin levels, time or activity of prothrombin, and fibrinogen levels. Serum alkaline phosphatase was elevated in normoalbuminemics and gamma-glutamyltransferase in patients with lowered prothrombin activity. Hypoalbuminemia was associated with hypofibrinogenemia, hypotransferrinemia with elevated aspartate aminotransferase or gamma-glutamyltransferase, and hypertransferrinemia with elevation of alanine aminotransferase. These data indicated the occurrence of hepatic dysfunction due to liver damage caused directly by alcohol or by alcoholism-associated nutritional deficiencies.